Communication and democratic reform in South Africa - Horwitz, Robert Britt (Communication, society, and politics., 2001)
The book examines the reform of the communication sector in South Africa in the transition from apartheid to democracy. It studies the complex political process by which broadcasting, telecommunications, the state information agency, and the print press were transformed from apartheid-aligned apparatuses to accountable democratic institutions.